The Impact of Tunneling Incentive Bonus Mechanism and Debt Covenant on Transfer Pricing - Aliyah, Siti; Fatmala Indriani, Riska (Action Research Literate, 2024)
Transfer pricing decisions are influenced by several factors, one of which is tunneling incentives. This study aims to determine the influence of Tunneling Incentives, Bonus Mechanisms, and Debt Covenants on Transfer Pricing. This study analyzes manufacturing companies listed on the Indonesia Stock Exchange. In this study, the input data comes from the company's annual report which is a research sample starting from 2018-2021 with criteria so that a total sample of 15 companies is obtained. Furthermore, the input data will be processed according to quantitative methods. The data analysis technique uses descriptive statistics, classical assumption tests, multiple linear regression tests and hypothesis testing. The results of this study show that the following variables: (1) Tunneling Incentive have a negative and significant influence on Transfer Pricing; (2) The Bonus Mechanism has a negative and significant effect on Transfer Pricing; (3) The Debt Covenant has a positive and significant effect on Transfer Pricing. Based on the results of the analysis and discussion, it can be concluded that the Tunneling Incentive has a negative and significant influence on Transfer Pricing, which means that the higher the tunneling incentive, the lower the transfer pricing carried out by the company.